Distribution policy and creation of shareholders' wealth : a study of firms listed on the Johannesburg Stock Exchange - Wolmarans, H.P. (Hendrik Petrus) (University of Pretoria, 2019)
Thesis (PhD)--University of Pretoria, 2019.